Carbon Emissions Disclosure and Environmental Performance on Company Value - Bintang Berliana Sibarani; Widia Agustina (Universitas Mercu Buana, 2023)
This study aims to identify the influence of carbon emissions and environmental performance disclosure on company value partially and simultaneously. The object of this research is a group of companies included in sustainable and responsible investment, the SRI-KEHATI Index in 2015-2020. The data analysis method is associative, using multiple linear regression analysis and partial and simultaneous hypothesis testing. The result indicates that carbon emissions disclosure has a partial and significant effect on enterprise value with the results of t-count 2.074 > t-table 2.05183 with a significance of 0.048 < 0.05. Environmental performance has a partial and substantial effect on company value with the results of t-count 4.624 > t-table 2.05183 with a significance of 0.000 < 0.05. Simultaneously, the carbon emissions and environmental performance disclosure have a significant effect on company value with the results of F-count 13,217 > F-table 3.34 with a significance of 0.000 < 0.05. The determinant coefficient shows that the variables in the study affect at the rate of 49.5%.